The Mediating Role of Posttraumatic Stress Symptoms in the Relationship between Adult Attachment and Quality of Life - Gianluca Santoro; Vittorio Lenzo; Alessandro Musetti; Cristiana Caneglias; Lina Rita Crimi; Lucia Sideli; Adriano Schimmenti (MDPI AG, 2024)
There is evidence that anxiety and avoidance toward close relationships (i.e., insecure attachment orientations), as well as posttraumatic stress symptoms (PTSSs), are linked to a poor quality of life. The current study aimed to investigate the potential mediating effects of PTSSs on the associations between insecure attachment orientations and domains of quality of life. A convenience sample of 497 adults (375 females, 75.5%), ranging in age between 18 and 65 years old (M = 32.48, SD = 13.26), was recruited. Participants were administered self-report instruments assessing attachment anxiety and avoidance, PTSSs, and domains of quality of life, including physical health, psychological status, social relationships, and environment. A series of mediation analyses were performed to test the mediating role of PTSSs in the relationships between attachment orientations and domains of quality of life. Results showed that attachment anxiety was related to decreased levels of quality of life in all domains, and that their associations were mediated by PTSSs. Also, attachment avoidance was related to a worse quality of psychological status and social relationships, and PTSSs were a significant mediating variable in these associations. Prevention programs and clinical interventions focused on promoting effective strategies for managing distress might be critical in reducing the impact of distressing events on the quality of life of individuals with insecure attachment.